Group Analysis of Q Values Calculated with Tangential Radius of Curvature from Human Anterior Corneal Surface - Zheren Xia; Chengmin Lin; Xueping Huang; Jinglu Ying; Mingguang Shi; Suilian Zheng (Journal of Ophthalmology)
Objective. To calculate the Q values from the human anterior corneal surface with the tangential radius of curvature and analyze its distribution characteristics in different age and refractive status groups. Methods. Tangential power maps of the anterior cornea from Orbscan II were acquired for 201 subjects’ right eyes. They were divided into groups of adults and children and then divided further into subgroups according to the refraction status. The Q values of each semimeridian were calculated by the tangential radius with a linear regression equation. The Q value distribution in both the nasal cornea and temporal cornea were analyzed. Results. The mean temporal Q values of the emmetropia group of adults and all children’s groups were significantly different from the mean nasal Q value. The mean nasal corneal Q values were more negative in children. The adult group showed differences only in the low myopia group. The mean Q value of the nasal cornea among different refractive groups of children was significantly different, and so was the temporal cornea between the adult myopia and emmetropia group. Conclusion. The method using the tangential radius of curvature combined with linear regression to obtain anterior surface Q values for both adults and children was stable and reliable. When we analyzed the anterior corneal Q value, area division was necessary.